1999
DOI: 10.3109/10826089909039409
|View full text |Cite
|
Sign up to set email alerts
|

Illegal Drug-Using Trends among Students in a Spanish University in the Last Decade (1984-1994)

Abstract: A sample of 2,086 university students in Valladolid (Spain) were surveyed in 1994 to assess their current use of illicit drugs. That information was used as a baseline to show the trends in the last decade in order to compare two other studies carried out on a similar target population in 1984 and 1990. Of those surveyed, 28.3% had taken some illicit drug within their lifetime, 16.7% in the previous year, and 7.2% in the previous month. Cannabis was the most common illicit drug used in the three levels among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Public health concern about hallucinogen use surfaced during the middle 20 th century in the U.S., but no longer is limited to this country. Concerns have been expressed in the United Kingdom, where 13% of university or college-attending students were found to have tried the mixed stimulant-hallucinogen methylenedioxymethamphetamine (MDMA, hereinafter ecstasy); corresponding estimates from the U.S. and Spain are 12.7% and 1.6%, respectively (Webb et al, 1996;Martinez et al, 1999;Johnston et al, 2003). Soellner (2005) has presented epidemiological evidence that ecstasy is now ranks second (behind marijuana) as the most preferred illegal drug among young people in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…Public health concern about hallucinogen use surfaced during the middle 20 th century in the U.S., but no longer is limited to this country. Concerns have been expressed in the United Kingdom, where 13% of university or college-attending students were found to have tried the mixed stimulant-hallucinogen methylenedioxymethamphetamine (MDMA, hereinafter ecstasy); corresponding estimates from the U.S. and Spain are 12.7% and 1.6%, respectively (Webb et al, 1996;Martinez et al, 1999;Johnston et al, 2003). Soellner (2005) has presented epidemiological evidence that ecstasy is now ranks second (behind marijuana) as the most preferred illegal drug among young people in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted in different regions of the globe reported that the prevalence of drug use was significantly reducing (Martinez, del Rio, Lopez, & Alvarez, 1999;Gfroerer, Greenblatt, Wright, 1997;Webb, Ashton, Kelly & Kamali, 1996;Thomas, Goddard, Hickman, & Hunter, 1993;Macfadden & Woody, 2000). Views about alcohol and other drugs and rates of use may vary among gender and age groups (Ogel, Tamar, Evren, & Cakmak, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…1 This fact has been brought to light by surveys on drug consumption, which showed a rise in prevalence among the general population between the ages of 15 to 64 years, 2 as well as among young adults aged 15-34 years. 3 The supply also increased, as shown by a rise in police seizures. 2 Within the European Union, treatment data showed that Spain has the highest figure of problematic cocaine use, followed by the Netherlands.…”
Section: Introductionmentioning
confidence: 99%